The problem of activation of the arhetype forms of the psyche of the individual in the process of the identification - Borovytska, О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Fenomenological attempt of the research of the problem of activation of arhetype forms as structural profound forms of the psyche of the individual at the moment of identification is demonstrated. A need to clarify a psychoanalytic essence of the category "identification" in the context of research on activation of archetype forms of the psyche is suggested. The actuality of archetype phenomenology is demonstrated as a fundamental methodological research of archetypes as structural universals of the psyche.
Keywords: identification; socialization; psyche; unconscious; archetype forms of the psyche; individual; patterns of behaviour; Self; motivation; profound psychology; the archetype phenomenology; intersubjective; psychotherapy